2020
DOI: 10.1007/s10864-020-09394-2
|View full text |Cite
|
Sign up to set email alerts
|

A Precision Teaching Framework for Improving Mathematical Skills of Students with Intellectual and Developmental Disabilities

Abstract: The aim of this study was to investigate the effect of a precision teaching (PT) framework on the mathematical ability of students with intellectual and developmental disabilities. We also examined if students of moderate mathematical ability could perform as well as their peers with fewer difficulties with their math skills. Sixteen students participated and were divided into three groups. One group engaged in PT, and the other two groups functioned as comparisons. The PT group practiced six skills introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Precision Teaching and its components have produced positive outcomes in various areas such as reading (Cavallini et al 2010;Hughes et al 2007;O'Brien et al 2018), writing (Datchuk et al 2015; and mathematics (Chiesa and Robertson 2000;McTiernan et al 2016;Vostanis et al 2020). One component, however, that has not been evaluated thoroughly is the goal-setting procedures utilized within a Precision Teaching framework.…”
Section: Introductionmentioning
confidence: 99%
“…Precision Teaching and its components have produced positive outcomes in various areas such as reading (Cavallini et al 2010;Hughes et al 2007;O'Brien et al 2018), writing (Datchuk et al 2015; and mathematics (Chiesa and Robertson 2000;McTiernan et al 2016;Vostanis et al 2020). One component, however, that has not been evaluated thoroughly is the goal-setting procedures utilized within a Precision Teaching framework.…”
Section: Introductionmentioning
confidence: 99%
“…In this longitudinal study, the ISI-Math tool was utilized to facilitate the instructional process via algorithm-based interventions and support students who struggle with diverse mathematical tasks. The evaluation outcomes revealed significantly better results in students' mathematical achievements and further illustrated the importance of technology in supporting daily instruction with high accuracy and precision [52]. Another field of application that PE has supported concerns the quality improvement of the teacher education programs and, more precisely, the equity across teachers' knowledge in mathematics.…”
Section: Educational Applicationsmentioning
confidence: 83%
“…Two studies reported frequency building as a component of the intervention alongside additional instruction beforehand (Datchuk, 2017; Datchuk & Kubina, 2017). One study reported frequency building as a component of intervention after untimed practice (Vostanis et al., 2020). Direct Instruction was implemented in two studies (Elliot et al., 2010; Kubina et al., 2009); however, it was unclear if frequency building was conducted in Elliot et al.‘s study in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Only sixteen studies reported the duration of sessions (57%) and one study did not report intervention intensity (4%). Only two studies indicated the maximum number of timings that were conducted during each intervention session (Lambe et al., 2015; Vostanis et al., 2020). Table 1 summarizes intervention intensities reported in each study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation